2011
DOI: 10.1002/pola.24571
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(tert‐butyl methacrylate)‐graft‐poly(dimethylsiloxane) graft copolymers via reversible addition‐fragmentation chain transfer polymerization

Abstract: Well‐defined poly(tert‐butyl methacrylate)‐graft‐poly (dimethylsiloxane) (PtBuMA‐g‐PDMS) graft copolymers were synthesized via reversible addition‐fragmentation chain transfer (RAFT) copolymerization of methacryloyl‐terminated poly (dimethylsiloxane) (PDMS‐MA) with tert‐butyl methacrylate (tBuMA) in ethyl acetate, using 2,2′‐azobis(isobutyronitrile) (AIBN) as the initiator and 2‐cyanoprop‐2‐yl dithiobenzoate as the RAFT agent. The RAFT statistical copolymerization of PDMS‐MA with tBuMA is shown to be azeotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Silicone-acrylic block, segmented and graft copolymers and interpenetrating networks have also been extensively investigated . In addition to basic studies on the composition dependent structure-morphology-surface behavior (270,274,276,281,282,284,285,290), these materials were also investigated as protective coatings (271,279,287), adhesives (273,277,283), membranes (286,288,289)and biomaterials (268,272).…”
Section: Figure 19mentioning
confidence: 99%
“…Silicone-acrylic block, segmented and graft copolymers and interpenetrating networks have also been extensively investigated . In addition to basic studies on the composition dependent structure-morphology-surface behavior (270,274,276,281,282,284,285,290), these materials were also investigated as protective coatings (271,279,287), adhesives (273,277,283), membranes (286,288,289)and biomaterials (268,272).…”
Section: Figure 19mentioning
confidence: 99%
“…[30][31] There are limited reports on branched PDMS polymers. [30][31][32][33][34][35][36] RAFT polymerization of methacrylate-terminated PDMS has produced bottlebrush PDMS with side-chain M n of 1 or 4.3 kg/mol and backbone degree of polymerizations (DP) up to 70 for the shorter side-chains. [32][33] Masuda et al 34 reported branched PDMS material with M w up to 349 kg/mol but with broad molecular weight dispersity (Đ = 1.7 -3.2).…”
Section: Introductionmentioning
confidence: 99%
“…Monofunctional macromonomers with one terminal polymerizable group are frequently used to prepare graft copolymers via copolymerization with low molecular weight monomers (see e.g., refs 28–44. and references therein).…”
Section: Introductionmentioning
confidence: 99%